2020
DOI: 10.21608/smj.2020.35598.1175
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in young versus elderly clinical characteristic and in hospital mortality a retrospective cross-sectional study

Abstract: Background and purpose About 10-15%of all ischemic strokes occur in young adults ,limited researches have specifically addressed stroke in the young, also, the etiology of ischemic stroke in the young are heterogeneous and can be relatively uncommon the purpose is to identify different risk factors of stroke in young and elderly and predictors of in hospital mortality patient and method: consecutive 197 patient with acute ischemic stroke admitted to neurology department, Sohag university hospital subdivided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…Traditional risk factors, that is, hypertension, diabetes and atrial fibrillation, were more prevalent in our very old stroke patients, similar to other studies 6,7,9,10 . The presence of such co‐morbidities may make management of stroke particularly more difficult.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Traditional risk factors, that is, hypertension, diabetes and atrial fibrillation, were more prevalent in our very old stroke patients, similar to other studies 6,7,9,10 . The presence of such co‐morbidities may make management of stroke particularly more difficult.…”
Section: Discussionsupporting
confidence: 86%
“…3 Traditional risk factors, that is, hypertension, diabetes and atrial fibrillation, were more prevalent in our very old stroke patients, similar to other studies. 6,7,9,10 The presence of such co-morbidities may make management of stroke particularly more difficult. In contrast, however, a previous cohort study reported hypertension, diabetes and smoking as having a relatively higher association with younger age, while risk from atrial fibrillation appeared to remain constant across age group.…”
Section: Practice Impactmentioning
confidence: 99%